Program Gerakan Nasional Literasi Digital (GNLD): Upaya Pemerintah Indonesia Dalam Mewujudkan Sustainable Development Goals (SDGs) 2030 - Banyu Hikmah; Ridho Anshori Muaz; Ichsan Fauzi Rachman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Digital literacy has become crucial in the current era of globalization and digitalization. In response to this, the Ministry of Communication and Information Technology launched the National Digital Literacy Movement (GNLD). This research aims to analyze the effectiveness of the National Digital Literacy Movement (GNLD) in improving digital literacy in Indonesia and its contribution to the Sustainable Development Goals (SDGs) 2030. The study employs a literature review method by analyzing articles, news, and various other publications published between 2017-2024 related to GNLD. The analysis shows that the National Digital Literacy Movement (GNLD) has successfully increased awareness and digital skills across various layers of society, especially in urban areas. This program also contributes to the Sustainable Development Goals (SDGs) 2030, including no poverty, quality education, gender equality, justice, and reduced inequalities. However, challenges remain in implementing GNLD, such as uneven access to technology and local cultures in some areas that do not support the initiative. The National Digital Literacy Movement (GNLD) is a highly strategic program with a significant contribution to achieving the SDGs 2030. Efforts to enhance and evaluate the program are necessary to ensure that its benefits can be equitably experienced by all segments of society.